Effective bioconversion of sewage treatment plant sludge by pure bacterial culture: an optimization study - Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Jami, Mohammed Saedi; Mansor, Mariatul Fadzillah (The Malaysia Association, 2020)
to evaluate the effective and efficient bioconversion through the process conditions. A 2-level full factorial (24 ) design with four central points was conducted with the aim of optimization of processes conditions such as temperature, agitation, pH and inoculum for the bioconversion of STP sludge through chemical oxygen demand (COD) removal (response). A second order polynomial model was developed to represent the removal of COD with the variation of different process conditions in the sludge treatment. Analysis of variance (ANOVA) of full factorial design showed a high coefficient of determination (R2 ) of 0.90 indicating a satisfactory adjustment of the model with the experimental data. The linear and interaction effects among the factors were identified through the p- and t-test. Statistical analysis showed that the agitation and inoculum size have significant effects (p<0.05) on bioconversion of STP sludge (COD removal). The results with the surface response analysis indicated the optimum values of parameters with the minimum content of COD (30 mg/L): temperature, 40℃; agitation, 50 rpm; pH, 3; inoculum, 5% (v/v).